Evaluation Serum Copper Levels in Preeclampsia and Healthy Pregnant Women - Baral, Nilima; Haque, Rezwana; Mishu, Farzana Akonjee (BIRDEM Medical Journal, 2019)
Background: Preeclampsia is a fatal medical disorder of pregnancy. It has been associated with adverse course and outcome of the pregnancy resulting in increased maternal and infant mortality and morbidity. As the pathogenesis of preeclampsia is not completely understood, prevention remains a complex issue. In recent times, there has been an increasing prevalence in the incidence of preeclampsia globally. The aim of this study is to determine the states of the copper in pregnant women with preeclampsia. Methods: This case-control study was carried out in the Department of Biochemistry, Mymensingh Medical College, Mymensingh, from July 2013 to June 2014. The subjects were selected on the basis of inclusion and exclusion criteria by purposive method. This study included 73 patients with preeclampsia as case (Gr.I) classified into two subgroups according to the gestational age: Gr.I(a); preeclampsia in the second trimester (n = 35), and Gr.I(b); preeclampsia in the third trimester (n = 38). Copper levels were analyzed and results were compared with 73 apparently healthy pregnant control (Gr.II), and the corresponding gestational age subgroups [Gr.II(a); normal pregnancy of second trimester (n = 35) and Gr.II(b), normal pregnancy of third trimester (n = 38)]. Results: The mean serum copper level was significantly (p<0.001) lower in case group than that of control group. Similar extent of reduction was observed in serum copper level at different gestational age groups of preeclamptic women when compared with corresponding control groups. Conclusion: Estimation of serum copper level should be incorporated in pre eclamptic patients for prevention of complications. Birdem Med J 2019; 9(1): 18-22